The experience of using prompting technology from the perspective of people with Dementia and their primary carers. (3rd August 2021) - Evans, N.; Boyd, H.; Harris, N.; Noonan, K.; Ingram, T.; Jarvis, A.; Ridgers, J.; Cheston, R.
Abstract: Objectives: People who are living with dementia typically experience difficulties in completing multi-step, everyday tasks. However, digital technology such as touchscreen tablets provide a means of delivering concise personalised prompts that combine audio, text and pictures. This study was one component of a broader, mixed methods study that tested how an application (app) –based prompter running on a touchscreen tablet computer could support everyday activities in individuals with mild to moderate dementia. In this study we set out to understand the experiences of people living with dementia and their primary carer in using the prompter over a four-week period. Method: We collected qualitative data using semi-structured interviews from 26 dyads, composed of a person living with dementia and their carer. Dyads were interviewed at the start and end of this period. Transcripts were then analysed using thematic analysis. Results: The study identified three overarching themes related to: participants' attitudes towards the technology; their judgements about how useful the prompter would be; and the emotional impact of using it. Conclusion: Consistent with the Technology Acceptance Model, carers and participants were influenced by their approaches to technology and determined the usefulness of the prompter according to whether it worked for them and fitted into their routines. In addition, participants' decisions about using the prompter were also determined by the extent to which doing so would impact on their self-identity.